THE PROBLEM OF EARLY MARRIAGE REVIEWED FROM THE PERSPECTIVE OF EDUCATION, SOCIO-CULTURE AND MARRIAGE LAW IN SEMARANG CITY - Sukamto, Sukamto; Masyhar, Ali; Waluyo, Edi (Jurnal Meta-Yuridis, 2025)
Early marriage causes problems, both from an educational and socio-cultural perspective and in the Marriage Law. Regarding the age limit for marriage, the Marriage Law refers to Article 7 paragraph 1 of 1974 which was later revised and became the Marriage Law Number 16 of 2019. Developmental theory explains that the adult phase is when individuals try to fulfill the most important social needs, namely having a romantic partner, husband or wife. However, at the age of 16-19 years, individuals are still in a stage of development that is not fully mature, both physically and mentally. The formulation of the problem raised in this study is; (1) The sociological impact of early marriage, (2) What preventive efforts can be made to overcome early marriage in Semarang City? The results of the study show that early marriage is caused by several factors including economic, socio-cultural and educational factors. This study also produces preventive efforts that can be made to overcome these problems. The problems of early marriage in Semarang City require preventive efforts to overcome them